EFFICIENCY OF DIFFERENT MOISTURE AND NUTRITION CONDITIONS IN EARLY POTATO GROWING UNDER DROP IRRIGATION IN SOUTHERN UKRAINE - Boiarkina, Liubov; Vozhehova, Raisa; Balashova, Halina; Yuzyuk, Olesya; Yuzyuk, Sergey; Kotov, Borys; Kotova, Olena (Journal of Agricultural Sciences (Belgrade), 2021)
The article presents the results of field research the effectiveness of different moisture and nutrition conditions at the cultivation of early potato under drip irrigation in southern Ukraine. The scheme of the experiment included treatment with the complex Mochevyn K as an additional control and different methods and correlation of fertilizers Rlantafol (treatment of tubers before planting, fertilizing on shoots, in budding and their combination), as well as different soil moisture conditions (replenishment of moisture deficit in 100 and 200 m³/ha). Studies have shown that the average yield of early harvest potato without irrigation was 10.44 t/ha. Moisture conditions significantly affected the yield of young tubers – irrigation at a rate of 200 m³/ha provided 21.61 t/ha, reducing the irrigation rate to 100 m³/ha led to a decrease in yield to 19.86 t/ha. One-time treatment of planting tubers, treatment of plants during germination and during budding provided almost the same yield. Two- and three-time treatments of plants and tubers did not lead to a significant increase yield. The highest productivity of potato was provided by the treatment of tubers with the Plantafol and the combination of tubers and plants treatment at shoots on the background of 200 m³/ha irrigation on average for two years, respectively, 24.16 and 23.22 t/ha.
Keywords: potato seed material, early harvesting, water consumption, tuber treatment, foliar feeding